Short Dental Implants (6 mm) Versus Standard Dental Implants (10 mm) Supporting Single Crowns in the Posterior Maxilla and/or Mandible: 2-Year Results from a Prospective Cohort Comparative Trial - Luigi Svezia; Filippo Casotto (Stilus Optimus, 2018)
Objectives: The purpose of present study was to compare short (6 mm) with longer implants with the same surface use in the posterior maxilla and/or mandible. Material and Methods: A total of 110 implants of 6 or 10 mm in length were placed with an internal hex (n = 60) and with a conical connection (n = 50) but the same material, surface and design, supporting single crowns in the posterior maxilla and/or mandible. Outcomes measured were implant survival and marginal bone level changes up to 24 months after loading. Results: Final group consisted of 105 implants: 6 mm (n = 58) and 10 mm (n = 47). Success rate after 24 months was similar between treatment groups (98.3% vs. 100%; P = 0.361). Failure rates of the short implants in mandible (1/18, 5.6%) and in maxilla (0/40, 0%) were also not significantly different (P = 0.133). Success rate after 2 years was similar between internal hex vs. conical connection implants (100% vs. 97.7%; P = 0.233). Subjects lost statistically significant marginal peri-implant bone in both groups, but without differences (6 mm group: 0.38 mm [95% CI = 0.09 to 0.67] vs. 10 mm group: 0.43 mm [95% CI = 0.15 to 0.61]; P = 0.465 at 24 months), in relation also to type of implant (internal hex vs. conical, P = 0.428 at 24 months) or operator (P = 0.875 at 24 months). Conclusions: Short implants may be successful in the posterior areas during the first 24 months of loading, with similar outcomes to 10 mm long implants, supporting their use as a valid option in selected cases. However, larger and longer follow-ups of 5 years or more are needed.